2022
DOI: 10.3390/ijms231911502
|View full text |Cite
|
Sign up to set email alerts
|

miRNA: A Promising Therapeutic Target in Cancer

Abstract: microRNAs are small non-coding RNAs that regulate several genes post-transcriptionally by complementarity pairing. Since discovery, they have been reported to be involved in a variety of biological functions and pathologies including cancer. In cancer, they can act as a tumor suppressor or oncomiR depending on the cell type. Studies have shown that miRNA-based therapy, either by inhibiting an oncomiR or by inducing a tumor suppressor, is effective in cancer treatment. This review focusses on the role of miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 212 publications
1
88
0
Order By: Relevance
“…A major prerequisite to achieve this is the development of miRNA modifications and sophisticated delivery systems, which enable a high efficiency and specificity of miRNA-based therapeutics. 48 , 49 Moreover, it has to be guaranteed that such therapeutics are safe and do not induce severe side effects in patients. 50 , 51 Tremendous progress in miRNA bioengineering, nanotechnology, and viral vector development may markedly contribute to fulfilling these criteria in future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A major prerequisite to achieve this is the development of miRNA modifications and sophisticated delivery systems, which enable a high efficiency and specificity of miRNA-based therapeutics. 48 , 49 Moreover, it has to be guaranteed that such therapeutics are safe and do not induce severe side effects in patients. 50 , 51 Tremendous progress in miRNA bioengineering, nanotechnology, and viral vector development may markedly contribute to fulfilling these criteria in future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main issue still remains in the off-target effects of miR-based therapeutics, which need to be addressed in order to reduce their toxicity without affecting their therapeutic effects. To date, only 10 miR-based molecules have been tested in clinical trials and none of them has entered into phase III clinical trials [ 37 ].…”
Section: Ncrnas In Posttranscriptional Regulationmentioning
confidence: 99%
“…The obtained proteins encoded by 28 m7G-related genes play multiple roles in m7G biological processes, which in turn affect cancer progression [8][9][10][11]. It has been demonstrated that miRNAs regulate gene expression posttranscriptionally [12]. miRNAs can affect tumor progression by regulating the expression of downstream m7G-related genes [13,14].…”
Section: Construction Of the M7g-related Mirna Prognosismentioning
confidence: 99%